How strong is the business-to-business brand in the workforce? An empirically-tested model of 'internal brand equity' in a business-to-business setting - (:unkn) unknown (ELSEVIER SCIENCE INC, 2010)
In the business-to-business sector the brand-owner s employees are increasingly playing a key role in the representation of individual and corporate brands at the interface with actual and potential customers Consequently Internal branding has recently emerged as an important issue in industrial markets This article proposes and empirically validates a theoretically structured framework for the measurement of a new construct internal brand equity and identifies its determinants and consequences The findings offer evidence for the powerful impact of a brand-oriented corporate culture on internal brand equity and demonstrate its relationship to external brand equity Conclusions are drawn for management practice and future research (C) 2010 Elsevier Inc All rights reserved
Keywords: Brand strategy; Brand orientation; Brand equity; Business to business brand; Internal branding; ORGANIZATIONAL CITIZENSHIP BEHAVIORS; CUSTOMER SATISFACTION; EMPLOYEE BEHAVIOR; CORPORATE CULTURE; SCALE DEVELOPMENT; JOB-SATISFACTION; PERFORMANCE; COMMITMENT; METAANALYSIS; ANTECEDENTS